Indonesia’s Innovation Policies: Evolution and Institutional Structure - Togar M. Simatupang; Fitriani Tupa R Silalahi; Liane Okdinawati; Widya Nandini; Putu Franciska Fajarini (STI Policy and Management Journal, 2022)
Along with world developments that encourage every country to innovate, Indonesia also has aspirations to increase domestic innovation. The success of several other countries in increasing economic growth through innovation is the driving force. Indonesia also has the same desire to pay attention to innovation and science, and technology. Along the way, there have been developments in innovation policies in Indonesia in terms of institutional structure and implementation of innovative programs. This paper tries to identify how the innovation policy has developed through quantitative analysis of innovation, science and technology regulations starting in 2004. This paper has divided the regulations into four eras according to the era of the elected President from 2004 to 2024. A multi-dimensional quantitative methodology is carried out to examine Indonesia's innovation policies. The policy search is carried out by searching for regulations in two Indonesian regulatory databases. From the analysis results, it is found that Indonesia has driven S&T and innovation policies, including policies that support innovation funding and has made several changes to the formation of innovation organizations to produce better coordination between researchers who create innovative products and industries as users.